2011
DOI: 10.1051/0004-6361/201015057
|View full text |Cite
|
Sign up to set email alerts
|

A statistical-mechanical explanation of dark matter halo properties

Abstract: Context. Cosmological N-body simulations have revealed many empirical relationships of dark matter halos, yet the physical origin of these halo properties still remains unclear. On the other hand, the attempts to establish the statistical mechanics for self-gravitating systems have encountered many formal difficulties, and little progress has been made for about fifty years. Aims. The aim of this work is to strengthen the validity of the statistical-mechanical approach we have proposed previously to explain th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Based on the dynamical similarities between self‐gravitating systems and fluids, we further confirm the validity of fluid‐like entropy for self‐gravitating systems. Also, we improve the variational calculation of our previous work (Kang & He 2011), and propose an index‐varying polytropic structure, which has finite mass and can be obtained under the assumption of incomplete relaxation. If we treat the equation of dynamical equilibrium as a differential constraint to the entropy, we derive a similar equation to White & Narayan (1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the dynamical similarities between self‐gravitating systems and fluids, we further confirm the validity of fluid‐like entropy for self‐gravitating systems. Also, we improve the variational calculation of our previous work (Kang & He 2011), and propose an index‐varying polytropic structure, which has finite mass and can be obtained under the assumption of incomplete relaxation. If we treat the equation of dynamical equilibrium as a differential constraint to the entropy, we derive a similar equation to White & Narayan (1987).…”
Section: Discussionmentioning
confidence: 99%
“…However, in this paper we will argue about the validity of their calculation. Our previous works (He & Kang 2010; Kang & He 2011, hereafter KH11) employed this entropy form to study the equilibrium configurations of dark matter haloes. Moreover, KH11 considered the general anisotropic situation and found an equation of state whose density profile has finite mass and extent.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is necessary to return to the fundamentals of statistical mechanics and develop special techniques to handle the long‐range nature of gravity (Padmanabhan 1990; Chavanis 2006). In our earlier two works (He & Kang 2010; Kang & He 2011), we performed preliminary investigations into the statistical mechanics of collisionless self‐gravitating systems, and found that both the concept of entropy and the entropy principle are still valid for self‐gravitating systems, which implies that an entropy‐based statistical mechanics of self‐gravitating systems is feasible.…”
Section: Introductionmentioning
confidence: 99%
“…In a follow‐up work (Kang & He 2011), by introducing an effective pressure instead of a radial pressure to construct the specific entropy, we used the entropy principle. We proceeded in a similar way as in He & Kang (2010) and we obtained a new entropy stationary equation.…”
Section: Introductionmentioning
confidence: 99%
“…Entropy is extensive. We first constructed the specific entropy, and then obtained the total entropy in the additive and hence extensive way, as in of He & Kang (2010) or of Kang & He (2011). The fact that such an extensively defined entropy works very well indicates that a non‐extensive entropy, such as the entropy of Tsallis (1988), is not necessary. The equilibrium states also consist of mechanical equilibrium.…”
Section: Introductionmentioning
confidence: 99%